Acrylamide, a toxic maillard by-product and its inhibition by sulfur-containing compounds: A mini review - Augustine, Dahryn Andilla; Bent, Grace-Anne (Frontiers in Food Science and Technology, 2022)
The Maillard reaction not only results in the formation of flavor compounds, but also harmful by-products, including the infamous toxicant acrylamide. Dietary acrylamide cannot be eliminated, but its levels in foods can be minimized. This review discusses the mechanisms of inhibition, effectiveness under varied conditions, and limitations of the sulfur-containing compounds: thiols, sulfites, thiosulfinates, and thioethers. These compounds have proven to be effective inhibitors of acrylamide formation. Among these compounds, the thiols are deemed the most effective. However, such success is masked by their negative effects on food taste and odor.